SAT0285 Progranulin-Neutralizing Autoantibodies in Psoriatic Arthritis. (23rd January 2014) - Assmann, G.; Zinke, S.; Zaks, M.; Pfoehler, C.; Preuss, D.; Pfreundschuh, M.; Thurner, L.
Abstract : Background: Psoriatic arthritis (PsA) is a distinctive inflammatory arthritis that may develop in 5-40% of individuals suffering from psoriasis. We recently described progranulin autoantibodies (PGRN-Abs) in the sera of patients with different autoimmune diseases including seronegative polyarthritis [Ref. 1 ]. Objectives: In the present study we investigated the occurrence of PGRN-Abs in PsA. Methods: PGRN-Abs were determined in 260 patients with PsA, 100 patients with psoriasis without arthritic manifestations and 97 healthy controls using a recently described ELISA. PGRN plasma levels were determined from subgroups by a commercially available ELISA-kit. Results: PGRN-Abs were detected in 50/260 (19.23%) patients with PsA, but in 0/100 patients with psoriasis without arthritic manifestations (*p=0.0001) [Figure 1 ]. PGRN-Abs were significantly more frequent in PsA patients with enthesitis (21.3 vs. 14.7%) or dactylitis (21.8 vs. 15.4%). PGRN-Abs were also more frequent in PsA patients receiving treatment with TNF-α-blockers than in patients treated without TNF-α-blockers (20.8 vs. 17.4%; p=0.016). PGRN plasma levels were significantly lower in PGRN-Ab-positive patients with PsA than in healthy controls and patients with psoriasis without arthritic manifestations (p<0.001), indicating a neutralizing effect of PGRN-Abs. Image/graph: Conclusions: PGRN-Ab is a serological marker present in a subgroup of patients with PsA, but absent in patients without arthritic manifestations. Its restriction to patients with PsA suggests that PGRN-Ab might not only be useful as a diagnostic and prognostic marker, but may be involved in the pathogenesis of the arthritic process in a subgroup of patients with PsA. References: Thurner L, Preuss KD, Fadle N, Regitz E, Klemm P, Zaks M, Kemele M, Hasenfus A, Csernok E, Gross WL, Pasquali JL, Martin T, Bohle RM, Pfreundschuh M. Progranulin antibodies in autoimmune diseases. J Autoimmun. 2012 Nov 11. doi:pii: S0896-8411(12)00130-8. 10.1016/j.jaut.2012.10.003. [Epub ahead of print] Disclosure of Interest: None Declared